My little Chickadee - Skinner, Frank 1897-1968 (Universal Studios, 2006)
Flower Belle Lee is run out of Little Bend after suspicions arise that she's connected to the Masked Bandit. She meets con man Cuthbert J. Twillie and pretends to marry him. Jeff Badger, the town boss, names Cuthbert J. Twillie the town sheriff when Twillie and Flower Belle arrive in Greasewood city.
Bildformat 4:3 full frame
Orig.: USA 1940
Keywords: Feature films; Western -- Film; Film